RESPON PERTUMBUHAN DAN PRODUKSI TANAMAN JAGUNG MANIS TERHADAP KEPADATAN POPULASI DAN JENIS PUPUK KANDANG - Edy Edy; Andi Ralle; Suherah Suherah; Sudirman Numba; Hasriani Hasriani (Percetakan Umi Toaha Makassar, 2023)
Sweet corn is a type of corn that has special characteristics because of its high sugar content so it can be used in various types of food, including snacks, various kinds of vegetables, corn sugar, and so on. Based on this, the demand for sweet corn is increasing so efforts are needed to increase production by increasing the correct population density per unit area and using the right type of manure. This study aims to get the population density and the right type of manure to increase the growth and production of sweet corn plants. This research was conducted in Lera Village, Wotu District, East Luwu Regency, South Sulawesi Province, starting in July-October 2019. This research used a factorial of 2-factor of the randomized block design method. The Factor I: population density (P) consists of 3 levels, namely: P1 (one plant per clump), P2 (two plants per clump), P3 (three plants per clump), and factor II is the type of manure (A) with 3 types, namely: A1 (chicken manure 15 t/ha), A2 (cow manure 15 t/ha), A3 (goat manure 15 tons/ha), so that 9 treatment combinations were obtained, repeated 3 times. The results showed that the interaction of two plants per clump and the application of chicken manure gave the best results on cob production with husks per hectare.